Domestic violence in a southern city: The effects of a mandatory arrest policy on male-versus-female aggravated assault incidents - Truc-Nhu (American journal of criminal justice, 2000)
Studies attempting to measure the effects of a mandatory arrest policy in domestic violence situations have yielded somewhat contradictory results. This study examines the effects of such a policy in one southeastern city. It utilizes police records from 1993–1997 to generate a proportionate stratified sample of 442 aggravated assaults cases committed by male partners on female victims. Logistic regression was used to model arrest determinants before and after the new policy was adopted. Results show that while there was an increase in the number of domestic violence reports after the proarrest policy went into effect, the total number of reports continued to decrease. A comparison of arrest determinants before and after the new guidelines became effective indicates this policy did not affect arrest decisions.